(untitled) (Research, Society and Development, 2023)
The aim of this study was to analyze the role of the Hospital infection control committee in cases of multi-resistant bacteria. Methods: Bibliographic review, carried out between September and December 2018. The search for the articles was carried out in the Scielo, Lilacs, PubMed and Ibecs databases. The descriptors "Hospital Infection" and "multi-resistant bacteria" were chosen. Results: The managers of the institutions must be aware of the problem, since they do not provide direct care to the patient, but they provide subsidies for the practice to happen and are also responsible for performing a good job in the hospital environment, preventing and controlling infections. indirectly. Conclusion: Hospital infection control programs to be effective must meet the minimum established by legislation, having in their scope, actions such as data collection, administration, analysis and communication system with a continuous improvement plan; formal policies and procedures; and study, education and training programs.